PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS VIII SMP NEGERI 1 SUNGGUMINASA - Rahmat Saleh (STKIP Pembangunan Indonesia Makassar, 2017)
The study aims at examining (I) the influence of problem based learning model towards student’s motivation at SMPN I Sungguminasa, (2) the influence of problem based learning model towards student’s learning result at SMPN I Sungguminasa. This study is a quasi-experiment reseacrh. The population was the entire class VIII of the second semester of 2014/2015 academic year at SMPN I Sungguminasa. The samples were selected by employing random sampling technique by choosing 2 classes from the existing 12 classes. The samples obtained class VIII-I which taught by using problem based learning model with 41students. The results of the study reveal that (I)there signicant influence of problem based learning towards the student’s motivation at SMPN I Sungguminasa and (2) there is significant influence of problem based laerning towards the student’s learning result at SMPN I Sungguminasa.Keywords: Problem Based Learning approach, Motivation, Learning result